Development of Integrated Digital Pop-Up Book Media Using PBL Model for HOTS Science Literacy - Syakirah Adita; Gulmah Sugiharti (Universitas Negeri Medan, 2025)
Low Science Literacy and limited PBL-based learning media encourage the need for media development that can improve students' HOTS. This study aims to develop a Pop-Up Book Digital learning media integrated with the Problem-Based Learning model and test the validity and practicality of the media on stoichiometry material. This study uses the Research and Development (R&D) method with the ADDIE development model. The sample was 3 lecturers who are media and material experts from the chemistry department, 1 chemistry teacher, and students of Class X-C at SMAS Imelda Medan. The data collection instrument used a questionnaire adopted from BSNP based on the Likert Scale. The results of the study showed that the developed media was declared valid based on the average percentage of material experts of 85.15%, media experts of 98.33% and educator assessments of 88.54% with very high validity criteria. In addition, the developed learning media is included in the very good criteria reviewed from the response of students, with an average percentage of 87.89%. Thus, it can be concluded that the Pop-Up Book Digital media integrated with the Problem-Based Learning model can be used in chemistry learning of stoichiometry material at SMA Swasta Imelda Medan.